LES APPORTS DE LA CONSTITUTION POUR L'EUROPE À LA THÉORIE DU FÉDÉRALISME - Jacques Ziller (Revista d'Estudis Autonòmics i Federals, 2005)
This article analyzes the role thatin the medium and long term theTreaty establishing a Constitutionfor Europe will have eventually inthe process of European integration.In spite of the failed resultsof the French and Dutch referendafor its ratification, the Treaty,claims the author, will readopt acentral role in the future of theEuropean Union. From this perspective,the author explores differentaspects and features of theTreaty: he firstly deals with thedebate about the nature of theTreaty itself, that is, whether it isjust a treaty or whether it can beconsidered a constitution; secondly,the discusses about the possiblepolitical directions the Treatysets for Europe: whether it establishesa path for a federation, aconfederation or a third way. Thirdly,the author looks at other centralfeatures of the Treaty such asthe right of secession of the MemberStates, the recognition of nationalinstitutional structures, theestablishment of the EuropeanUnion’s institutions, the regulationof relations between the EuropeanUnion and the Member States,and the primacy principle.